Positive effects of ferric iron on the systemic efficacy of nephrilin peptide in burn trauma - Desmond D Mascarenhas; Amina El Ayadi; Puja Ravikumar; Gyeong Jin Kang; Tammy Langer; Carlos Moreno; Edward P Amento (SAGE Publishing, 2020)
Introduction: Nephrilin peptide is a designed inhibitor of Rictor complex (also known as mTORC2), an evolutionarily conserved assembly believed to modulate responses to cellular stress. We previously demonstrated the ability of nephrilin peptide to suppress neuroinflammation, loss of body mass, glycaemic control and kidney function in a rat scald model, as well as sepsis mortality in a mouse model. The present study explores the effect of nephrilin plus iron formulations on clinically relevant outcomes in the rat scald model. Methods: Animals were treated with nephrilin by subcutaneous bolus injection on post-burn days 1-7. Equimolar ferric iron in the formulation improved the positive systemic effects of nephrilin on kidney function, glycaemic control, oxidative stress, early hyperinflammation, late inflammasome activation, hyperangiogenesis and body mass, all variables previously shown to bear upon clinically relevant burn injury outcomes. The sparing effects of nephrilin-iron were demonstrated in both sexes. Discussion: Surprisingly, optimum daily treatment doses were in the range of 2-4 mg/kg, while 8 mg/kg was less effective, suggesting the possibility of marginal pro-oxidant effects from the 'free' iron fraction. Thus, although ferric iron in the nephrilin formulation is clearly helpful, care must be exercised to select an optimum treatment dose. Conclusion: Iron increases the efficacy of nephrilin peptide in burns.